Analisis Pola Penyelewengan Beban Perjalanan Dinas pada Kementerian di Indonesia Tahun 2015-2017 - Dyah Setyaningrum; Irfan Jeremi (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2020)
This study aims to analyze the pattern of official travel misappropriation, especially related to the pattern of the type of case that usually occurred, the misappropriation causes, and the follow-up process for recommendation given. The research samples are all ministries in Indonesia in the year of 2015-2017. The method used in this study is mixed method, which is a combination of quantitative and qualitative methods. The quantitative method’s purpose is to find the pattern from the type of case in general, then choosing and detailing the type of case with the greatest number of findings. The qualitative method’s purpose is to deepen the information related to the type of case studied. The result of this study shows that the type of case with the greatest findings is granting travel expenses not according to regulations. That case happened because the implementation of the functions and responsibilities of the officers who have a role in the payment and reporting process for official travel are not optimal. The solution to this problem is optimizing officers' roles through the implementation of three lines of defense.